Augmented reality in physical exercise - Saraiva, Luana Bittencourt; Santos, Bruno Raphael de Carvalho; Santos, Alef Vernon De Oliveira; Silva, Eduardo Jorge Lira Antunes Da; Dias, Lúcio Vasconcellos; Ruschival, Claudete Barbosa; Kuwahara, Nelson (DAT Journal, 2021)
Faced with the new coronavirus pandemic, initiatives capable of adapting to social isolation and remote operation technologies are relevant. Among the emerging technologies, Augmented Reality (AR) allows interaction between the real and virtual world, even helping people to have a healthier life. The article investigates how AR has been used to guide people in performing physical activity and takes place through prospecting in international databases to visualize the approach to the theme. The results showed two groups of applications in AR: gamification, played by the Pokémon Go game; and rehabilitation, with applications for the recovery of people with muscle loss. There is a predominance of publications originating in the United States and the United Kingdom, according to the search engine and defined string for conducting the prospecting research in journal collections. The information collected will help to define functionalities that can be used in RA applications.